THE EFFECT OF WORD MAP STRATEGY USING INSTAGRAM TO DEVELOP STUDENTS’ VOCABULARY - Qisti, Nurul (Journal of English Teaching, Literature, and Applied Linguistics, 2020)
Study on the use of Instagram has bloomed in EFL teaching learning process. Instagram is one of the favorite SNSs among students. This research aims to discover the effect using Instgram combined with Word Map strategy as learning tool in developing students’ vocabulary by involving 64 Islamic junior high school students. They were asked to do vocabulary level test to measure their mastery in vocabulary. In supporting the data, a questionnaire was also distributed to the treatment group. A quasi-experimental design was employed during the study. A two-way ANOVA was used to analyze the data. The findings revealed that applying Word Map strategy with Instagram significantly improved students’ vocabulary from 11% for the control group to 18.98% for the treatment group. Hence, developing Word Map strategy with mobile application integration to improve students’ writing skill within EFL curriculum is worth investigating.